X-ray diffraction and stress relaxations to study thermal and stress-assisted annealings in nanocrystalline gold thin films. (July 2019) - Godard, P.; Faurie, D.; Sadat, T.; Drouet, M.; Thiaudière, D.; Renault, P.O.
Abstract: The dependence on thermal history of the plasticity mechanisms occurring in nanocrystalline gold thin films is evidenced thanks to relaxation tests combined with in-situ synchrotron X-ray diffraction. The two techniques complement one another. The activation parameters show that the films deform mainly by dislocations and give indications about their mean free paths, whereas the Bragg peak positions, widths and areas bring invaluable information on residual stress as well as on some plasticity properties, like dislocation storage inside the grains or grain rotations. For the demonstration, two sputter-deposited nanocrystalline 50 nm-thin films deposited onto stretchable substrates are studied. It is shown that an as-grown sample (at a homologous temperature of 0.22) presents a stress-assisted annealing, thus decreasing its initial defect density, whereas if a thermal annealing (3 h at 200 ∘ C, corresponding to a homologous temperature of 0.35) has been applied to the sample before the tensile test, it deforms by conventional plasticity, and the dislocations are not stored inside the grains. These mechanisms lead to different work-hardening properties. This work shows how a moderate annealing can have a profound influence on the mechanical behaviour of these thin films. Graphical abstract: Image 1